Ramatroban for chemoprophylaxis and treatment of COVID-19: David takes on Goliath. (2nd January 2022) - Chiang, Kate C.; Rizk, John G.; Nelson, Deanna J.; Krishnamurti, Lakshmanan; Subbian, Selvakumar; Imig, John D.; Khan, Imran; Reddy, Srinivasa T.; Gupta, Ajay
ABSTRACT: Introduction: In COVID-19 pneumonia, there is a massive increase in fatty acid levels and lipid mediators with a predominance of cyclooxygenase metabolites, notably TxB2 ≫ PGE2 > PGD2 in the lungs, and 11-dehydro-TxB2, a TxA2 metabolite, in the systemic circulation. While TxA2 stimulates thromboxane prostanoid (TP) receptors, 11-dehydro-TxB2 is a full agonist of DP2 (formerly known as the CRTh2) receptors for PGD2 . Anecdotal experience of using ramatroban, a dual receptor antagonist of the TxA2 /TP and PGD2 /DP2 receptors, demonstrated rapid symptomatic relief from acute respiratory distress and hypoxemia while avoiding hospitalization. Areas covered: Evidence supporting the role of TxA2 /TP receptors and PGD2 /DP2 receptors in causing rapidly progressive lung injury associated with hypoxemia, a maladaptive immune response and thromboinflammation is discussed. An innovative perspective on the dual antagonism of TxA2 /TP and PGD2 /DP2 receptor signaling as a therapeutic approach in COVID-19 is presented. This paper examines ramatroban an anti-platelet, immunomodulator, and antifibrotic agent for acute and long-haul COVID-19. Expert Opinion: Ramatroban, a dual blocker of TP and DP2 receptors, has demonstrated efficacy in animal models of respiratory dysfunction, atherosclerosis, thrombosis, and sepsis, as well as preliminary evidence for rapid relief from dyspnea and hypoxemia in COVID-19 pneumonia. Ramatroban merits investigation as a promising antithrombotic and immunomodulatory agent for chemoprophylaxis and treatment.